ROLE OF WOMEN ENTREPRENEURSHIP IN MSME’S : A STUDY OF RAJASTHAN STATE - Ms. Vaishali Sharma; Dr. Ruma Bhadauria (International Journal For Research In Business, Management And Accounting, 2025)
The important contribution of women entrepreneurship in the Micro, Small, and Medium Enterprises (MSME) sector within Rajasthan, India, is investigated in this study article. Though they encounter particular difficulties that affect their potential and development, women entrepreneurs have become major drivers of the socioeconomic development of the state. This study looks at the elements motivating women to start businesses, the obstacles they run across, and the techniques helping them to be successful. By use of a mixed-method approach comprising surveys, interviews, and case studies from important areas of Rajasthan, this research clarifies the reasons, goals, and challenges of women in MSMEs. Important results underline how business development and sustainability are influenced by socio-cultural dynamics, access to financial resources, family support, and academic background. Furthermore, this study points forth particular government programs and non-governmental support networks that have helped women entrepreneurs. This study aims to evaluate the present situation of women entrepreneurs in the MSME sector.